PENANGANAN NON-PERFORMING FINANCE DALAM AKAD MUSYARAKAH DI BANK KALSEL SYARIAH - Hidayat, Muhammad Rifqi; Komarudin, Parman (Islamic Economics and Business Faculty of UIN Antasari, 2018)
Each financing has risks faced by banks and customers, including on musyarakah contracts. This can result in losses if not resolved, the bank must cover it first from the existing reserve fund in each bank in case of such problematic financing happen. On the other hand, the DSN has not specifically regulated the guidelines on handling non-performing financing on musyarakah contracts. While the questions about it continue to emerge.Therefore, it is needed to be clarified about how the practice undertaken by the bank in case of problematic financing, because it is very influential on the health of a bank.This research is field type and uses qualitative descriptive approach. The primary data in this study is about the Bank Kalsel Syariah, either through the official website, observation, or interviews with the bank. For the secondary data, the authors collect from various literature, especially from legislation such as the Compilation of Islamic Economic Law and MUI Fatwa.In this research, it is found that the Bank Kalsel Syariah has managed the problem financing settlement in this musyarakah contract through several phases, those phases are the cash payment, revitalization of financing through contract restructuring, settlement through guarantee, and lastly through legal court.